Decentralization in Indonesia a measure of innovation and change - Nurbaya, Siti (Philippine Journal of Public Administration, 2002)
This article explains why the unitary system of Indonesia is crucial for the success of decentralization. Furthermore, it expounds why it is misleading to consider federalism as an option for Indonesia in the future. We must bear in mind that any system of government (be it decentralized or federal) is only as good as the quality of governments that are elected to govern. In a strong unitary system like Indonesia, it is decentralization and not federalism which gives the system of government its stability. The study strongly suggests that through decentralization, regional community participation will flourish. Indonesia is large, with diverse peoples and equally diverse and complex sets of governing institutions. It has emerged out of four centuries of colonial rule and survived its transition to a republic. Decentralization is the ultimate framework for developing democracy. This will provide all the regions with the opportunity to shape good governance in Indonesia.